A double safety lock tumor-specific device for suicide gene therapy in breast cancer. (1st February 2020) - Piña, Maria J.; Girotti, Alessandra; Serrano, Sofía; Muñoz, Raquel; Rodríguez-Cabello, J. Carlos; Arias, F. Javier
Abstract: The complexity and continuous evolution of cancer make the design of novel strategies of treatment a constant challenge in biomedicine. Moreover, most of cancer treatments are still not tumor-specific and provoke high systemic toxicity. Herein we have developed a novel selective nanodevice to eliminate tumor cells while leaving healthy ones intact. To achieve this objective, a polyplex carrier, comprising an elastin like-recombinamer covalently conjugated to an aptamer and complexed with therapeutic DNA, was tested. This carrier forms a double-lock multifunctional device due to specific binding to a tumor cell marker and the selective expression of therapeutic DNA inside human breast-cancer cells. Due to the stability provided by ELRs, the homogeneous population of polyplexes obtained showed selective toxicity against cancer cells in in vitro and in vivo assay. Inhibition of tumor progression was detected early being very significant at the end point, with a dose-dependent reduction in tumor mass. Histological studies revealed a specific reduction in tumor parenchyma and in specific tumor cell markers. These results represent an important step toward the rational development of an efficient, safe and more specialized gene-delivery device for tumor therapy. Graphical abstract: Image 1 Highlights: The biocompatibility of the novel non-viral vector construct for the target cancer cells was confirmed. The aptamer binds to the aberrantly hypoglycosilated MUC1 located on the breast cancer-cell surface. Treatment of mice bearing breast tumors with therapeutic polyplex decreased tumor volume. The reduction in tumor volume was confirmed by weighing the tumors post-necropsy. The treatment acts in a specific and selective way on tumor cells, as demonstrated by evaluating the prognostic factors.